تحريض المخاض باستخدام الميزوبروستول في تمام الحمل - الأيوب, جهاد; عبد الرحمن, أحمد; الشاعر, آصف (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 100 مريضة قسمت إلى مجموعتين : الأولى 50 مريضة تم إعطاؤها الميزوبروستول 25 مكغ مهبليا" كل أربع ساعات . الثانية 50 مريضة تم إعطاؤها الاوكسيتوسين وجاءت النتائج كالآتي : إن للبروستاغلاندينات E1 دورا" بالغ الأهمية في إنضاج عنق الرحم وتحريض المخاض. فترة التحريض 2.5- 28ساعة في المجموعة الأولى6-24.5 ساعة في المجموعة الثانية أي بمعدل 15.25 ساعة في المجموعتين، نسبة نجاح التحريض 92% في المجموعة الأولى ,94% في المجموعة الثانية، نسبة القيصريات 10.8% في المجموعة الأولى و10.6% في المجموعة الثانية نسبة تألم الجنين 4.347% في المجموعة الأولى و4.25% في المجموعة الثانية ،نسبة نجاح التحريض عندما بيشوب 1-2 80% في المجموعة الأولى و60% في المجموعة الثانية، وبالتالي الميزوبروستول أكثر فعالية من الأوكسيتوسين عندما يكون العنق أقل نضجا" The study included 100 patients who were divided into two groups: Group 1 included 50 patients who were administered Misoprostol 25 mg vaginally every 4 hours. Group 2 included 50 patient who were prescribed Oxytocin. The results were as follows: - Prostaglandin E1 is an important factor for ripening cervix and inducing labor. -The duration of induction is 2.5-28 hours in the first group and 6-24.5 hours in the second, and the incidence is 15,25 in both groups. -The rate of induction success is 92 % in the first group and 94% in the second. -The rate of cesarean section is 10.8 % in the first group and 10.6% in the second. -The rate of fetal distress is 4.347% in the first group and 4.25% in the second. - When Bishopped 1-2, the rate of induction success 80% in the first group and 60% in the second. This means that Misoprostol is more effective than Oxytocin when the cervix uterine is not ripe .